Model Bisnis Start-Up Berbasis Teknologi Digital Dalam Industri Kreatif Seni - Selvi Amanda; Arif Laksono; Natania Nurafni; Osberth Sinaga (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
This study examines the digital transformation of the creative arts industry, focusing on how technologies such as Augmented Reality (AR), Virtual Reality (VR), and Non-Fungible Tokens (NFT) have altered the creation and marketing of artworks. Digital platforms have expanded market access for artists, opened new opportunities for more efficient business models with lower costs, and created greater possibilities for cross-disciplinary collaboration. In this context, digital technologies allow artists to reach a global audience and sell their works in more innovative and interactive formats, increasing audience participation in the creative process. However, these developments also face significant challenges, such as increasingly intense competition, rapidly shifting trends, and limitations in resources to optimally implement these technologies. Furthermore, while there are significant opportunities in the global market, some artists in Indonesia still face difficulties in accessing and utilizing the latest technologies. With the creative economy contributing 7.16% to Indonesia's GDP in 2018, this study aims to provide an overview of the dynamics of the arts industry in the digital era and explore potential strategies to support the development of a more adaptable creative ecosystem. These strategies include digital training, strengthening cross-sector collaboration, and enhancing digital infrastructure to facilitate the future growth of the creative arts industry.